Flexible Ureteroscopic Lithotripsy Based on the Concept of Enhanced Recovery after Surgery: A Single-Centered Retrospective Study - Shu, Ling; Ao P; Zhang, Zhenxin; Zhuo, Dong; Dong, Changbin (Urology Journal, 2022)
Purpose: To evaluate the efficacy of flexible ureteroscopic lithotripsy (FURSL) based on the concept of enhanced recovery after surgery (ERAS). Materials and Methods: This study retrospectively analyzed 435 patients diagnosed with upper urinary calculi between 2017-2020 and categorized them into ERAS (ERAS management) and control groups (traditional management). The operative time, postoperative ambulation time, postoperative hospital stay, the total cost of hospitalization, postoperative complications, and stone removal rate between the two groups were subsequently compared. Results: The FURSL procedure was successfully performed in 427 patients but failed in 4 patients of the ERAS group (n = 216) and 4 of the control group (n = 219). No postoperative complications occurred in either group except for fever and hematuria. There was no significant difference in postoperative fever and stone removal between the two groups (all P > .05). However, patients in the ERAS group had a shorter operative time, shorter postoperative ambulation time, less postoperative severe hematuria, shorter postoperative hospital stay, and lower total cost of hospitalization than those in the control group (all P < .05). Conclusion: FURSL, based on the concept of ERAS, is safe and reliable for the treatment of upper urinary calculi, with rapid postoperative recovery and a low cost of hospitalization. It is worthy of clinical promotion.